2015
DOI: 10.1073/pnas.1511269112
|View full text |Cite
|
Sign up to set email alerts
|

Placebo analgesia and its opioidergic regulation suggest that empathy for pain is grounded in self pain

Abstract: Empathy for pain activates brain areas partially overlapping with those underpinning the first-hand experience of pain. It remains unclear, however, whether such shared activations imply that pain empathy engages similar neural functions as first-hand pain experiences. To overcome the limitations of previous neuroimaging research, we pursued a conceptually novel approach: we used the phenomenon of placebo analgesia to experimentally reduce the first-hand experience of pain, and assessed whether this results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
228
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(249 citation statements)
references
References 61 publications
15
228
4
2
Order By: Relevance
“…29 and 30), and for pleasant touch (63). Other studies have also supported a simulationist view of empathy by exploiting the placebo analgesia effect, showing that placebo analgesia changes self pain as well as vicarious pain (64,65). Although these studies are consistent with a simulationist account, it remains possible that there exist additional processes that do not operate through self-other overlap that participate in the experience of empathy (15,30).…”
Section: Discussionmentioning
confidence: 83%
“…29 and 30), and for pleasant touch (63). Other studies have also supported a simulationist view of empathy by exploiting the placebo analgesia effect, showing that placebo analgesia changes self pain as well as vicarious pain (64,65). Although these studies are consistent with a simulationist account, it remains possible that there exist additional processes that do not operate through self-other overlap that participate in the experience of empathy (15,30).…”
Section: Discussionmentioning
confidence: 83%
“…For example, studies could directly compare hypnosis, placebo effects, observational learning and/or social information effects in the same subjects. Future studies could also investigate transfer and interactions between those different types of effects, and between different affective target states (see e.g., Rütgen et al, 2015). Another important aspect of comparison across modulatory effects will be to test similarity of brain pathways using fine-grained brain imaging methods such as multivariate pattern analysis (MVPA) and connectivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to placebo studies on pain, these studies suggest reductions in areas associated with emotional experience such as ACC and AI (Petrovic et al, 2005; Rütgen et al, 2015; Schienle et al, 2014), and often associated increased activations in prefrontal regions including OFC and dlPFC (Benedetti, 2014; Koban et al, in revision; Mayberg et al, 2002; Petrovic et al, 2005). …”
Section: Social Information Effects On Pain and Emotionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,4 The relative importance of each set of processes in the experience of pain empathy has been recently debated. Some authors propose that empathy for pain is based mainly on processes "functionally equivalent to those engaged by first-hand experience of pain" (i.e., shared representations between self and others), 5 whereas others argue that empathy relies instead on our capacity to adopt others' perspectives and infer their emotional states. 6 Previous questionnaire-based research in schizophrenia has suggested abnormalities both in the cognitive and the affective processes, as evidenced respectively by lower perspective taking and increased personal distress scores compared with controls on the Interpersonal Reactivity Index (IRI 7 ).…”
Section: Introductionmentioning
confidence: 99%